Identification of the Novel Host Protein Interacting With the Structural Protein VP1 of Chinese Sacbrood Virus by Yeast Two-Hybrid Screening - Zhang, Xiyan; Fei, Dongliang; Sun, Li; Li, Ming; Ma, YueYu; Wang, Chen; Huang, Sichao; Ma, Mingxiao (Frontiers in Microbiology, 2019)
Chinese sacbrood virus (CSBV) is the major cause of honeybee deaths and has led to the collapse of Apis cerana colonies. VP1, the structural protein of CSBV, shows the highest variation in the amino acid sequences among proteins from different CSBV strains as well as exhibits excellent immunogenicity. However, its function with host protein still remains unclear. To clarify its function with host protein, we screened out host cellular proteins that interact with VP1 using the membrane protein yeast two-hybrid system. In addition, we verified interactions between heat shock protein 70 (Hsp70) and VP1 using glutathione S-transferase pull-down and co-immunoprecipitation assays. Hsp70 expression in CSBV-infected larvae was upregulated compared with that in healthy larvae. VP1 and Hsp70 were colocalized in the cytoplasm and nucleus. The results demonstrate that the interaction between VP1 and Hsp70 probably influences CSBV proliferation or promotes host antiviral immunity in the course of viral infection.